Ultimobranchial gland of freshwater catfish, Heteropneustes fossilis, in response to calcitonin administration - Srivastav,Ajai K. (2009)
The absence o!!f a hypocalcemic effect of calcitonin (CT) in fishes has been suggested due to exceedingly high plasma levels of CT; the fish may be saturated with respect of circulating CT and therefore unable to respond to exogenously administered CT. Earlier it has been suggested that a hypocalcemic action of injected CT may be obscured by changes in the release of endogenous CT and other calcium regulating hormones. In this study we have used artificial freshwater, calcium-deficient freshwater and calcium-rich freshwater and injected the fish with CT. The aim behind selecting these media were (i) in calcium-deficient medium there would be reduced circulating levels of CT, (ii) in calcium-rich medium there would be diminished secretion of prolactin (this hormone is hypercalcemic in fish), and (iii) by keeping the fish in calcium-rich medium we can test the antihypercalcemic action of CT. Moreover, the present study would reveal the changes in the ultimobranchial gland (UBG) after keeping the fish in all the above three media and/or injecting the fish with CT. Freshwater catfish, Heteropneustes fossilis, were administered intraperitoneally daily with vehicle or 0.5 U/100g body wt of salmon calcitonin (CT) and kept in artificial freshwater, calcium-rich freshwater and calcium-deficient freshwater for 10 days. Blood samples were collected on 1, 3, 5, and 10 days following the treatment and analyzed for serum calcium levels. The ultimobranchial gland (UBG) was also fixed for histological studies on these intervals. In artificial freshwater there was no change in the serum calcium levels of calcitonin-injected fish. The ultimobranchial gland of calcitonin-injected fish exhibited a progressive decrease in the nuclear volume from day 5 onwards. On day 10 vacuolization in the gland was also noticed. In vehicle-injected fish (control) kept in calcium-rich freshwater hypercalcemia has been noticed which persists till the end of the experiment. In calcitonin-treated fish maintained in calcium-rich freshwater there is no change in serum calcium level as compared to vehicle-injected fish. In vehicle-injected fish the UBG depicts decreased staining response and increased nuclear volume at day 5. On day 10 the nuclear volume is further increased and few degenerating cells have been noticed. Calcitonin fails to induce any histological change in the UBG as compared to control. In vehicle-injected fish kept in calcium-deficient freshwater the serum calcium levels decrease from day 1 to day 3. The levels exhibit hypercalcemia on day 10. CT treatment to the fish kept in calcium-deficient freshwater evokes a decrease in the calcium levels on day 1 and day 3. A significant hypercalcemia has been noticed on day 5 and day 10. In vehicle-injected fish kept in calcium-deficient freshwater the UBG reveals a decreased staining response on day 10. In CT-injected fish maintained in calcium-deficient freshwater the UBG depicts an increased nuclear volume and few exhausted cells on day 10. It can be concluded that CT can provoke hypocalcemia only when the fish is kept in medium which reduces the circulating levels of this hormone. The UBG of the fish kept in different calcemic media responded in a manner to indicate that it produces hypocalcemic factor - CT.